Automating the Centralised Admission Process with Analytical Platform - Fernandes, Salvador; Ghantkar, Ruchi; Desai, Pranita; Nayak, Megha (International Journal of Computer Sciences and Engineering, 2025)
Admission Processes for degree colleges conduct the admissions in courses like Medicine, Dentistry, Engineering, Pharmacy, Architecture, Homeopathy, Bachelor of Science in Nursing, Ayurveda and Allied Health Science. As there is an increase in the number of students to seek admissions in various courses, it causes a terrible pressure on the admission committee to manage and control the admission process when done manually. Hence, our proposed computer-aided system helps the administrative body in various tasks of the admission process which includes a collection of student’s application forms, storing data safely and automatic sorting of data according to various categories etc. The automated computer-aided system facilitates the student to perform tasks online that include form filling and viewing the merit and eligibility list, checking the seat availability at the time of counseling. The system also provides an analytical mock test to the students. The students, who are not sure of which courses they can have a good aptitude at, can answer the same